DAMPAK PERBEDAAN WAKTU PEMOTONGAN TERHADAP OFFALS AYAM BROILER YANG DIPELIHARA DENGAN SISTEM CLOSED HOUSE - ARIANA I N. T.; BULKAINI . (Fakultas Peternakan Universitas Udayana, 2021)
This study aims to determine the impact of the difference in cutting time on the weight of offals (internal offals and external offals). The study used a completely randomized design (CRD) with three treatments and six replica- tions. The treatments were: Slaughter on the first day (W1), slaughter on the second day (W2) and slaughter on the third day (W3). The results of the study were that broiler chickens reared in a closed house system and slaughtered on the second and third days experienced a decrease in internal offals weight in the liver by 8.50 – 18.91% and on internal fat 36.74 – 60.77% (P<0.05). The difference in slaughter time did not cause a decrease in internal offal weight in the heart, intestines and gallbladder weight (P>0.05). External offals on the neck there was a weight loss of 4.01 – 8.04% as a result of the difference in slaughter time of 2 – 3 days (P<0.05). The difference in slaughter time had no impact on head weight and foot weight (P>0.05). The conclusion of this study is that the difference in slaughter time of 1-3 days causes a decrease in liver weight and internal fat (internal offals) and a decrease in neck weight (eksternal offals).